Monitoring of serum 25-(OH)D level in infants and its correlation with bone density and development: Correlations of 25-(OH)D to density and development of bone - Ming, Dan; Zheng, Rongxiu (Cellular and Molecular Biology, 2023)
Serum 25-hydroxyvitamin D (25(OH)D) is an indicator of nutritional status in the body. Vitamin D (VD) is important for promoting calcium and phosphorus absorption and bone health. This work investigated the correlation between 25(OH)D level and bone density and bone development in infants. the bone density in 150 infants aged 0 to 3 years was measured by ultrasound. Based on the values of bone density, the infants were grouped into a normal (N) group (n = 95) and an abnormal (ABN) group (n = 55). At the same time, serum 25(OH)D, calcium, phosphorus, alkaline phosphatase (ALP), and parathyroid hormone (PTH) levels were detected to analyze their correlations. 25(OH)D, calcium, and phosphorus levels in the ABN group were greatly decreased, while ALP and PTH levels were increased obviously, all presenting remarkable differences with those in the N group (P<0.05). 25(OH)D was positively linked with bone density (r=0.918, P<0.01), calcium level (r=0.316, P<0.05) and phosphorus level (r=0.209, P<0.05) but showed negative associations with ALP level (r=-0.428, P<0.01) and PTH level (r=-0.327, P<0.05). elevating 25(OH)D was crucial in reducing the incidence of abnormal bone density, bettering bone metabolism, and improving the bone health of infants.